2021
DOI: 10.3390/v13081465
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccine Effectiveness in Preventing Severe Outcomes in Patients Hospitalized with Laboratory-Confirmed Influenza during the 2017–2018 Season. A Retrospective Cohort Study in Catalonia (Spain)

Abstract: Seasonal influenza is a common cause of hospital admission, especially in older people and those with comorbidities. The objective of this study was to determine influenza vaccine effectiveness (VE) in preventing intensive care admissions and shortening the length of stay (LOS) in hospitalized laboratory-confirmed influenza cases (HLCI) in Catalonia (Spain). A retrospective cohort study was carried out during the 2017–2018 season in HLCI aged ≥18 years from 14 public hospitals. Differences in means and proport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…This suggests that vaccinated persons may have been less likely to be hospitalized with influenza during influenza seasons. Previous studies have shown that unvaccinated people hospitalized with influenza are more likely to develop severe outcomes compared with hospitalized, vaccinated patients who develop influenza [ 26–28 ]. One study found that significantly more unvaccinated people were admitted to the hospital or died and that vaccination reduced these rates by 23% in people aged 18 years and older [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that vaccinated persons may have been less likely to be hospitalized with influenza during influenza seasons. Previous studies have shown that unvaccinated people hospitalized with influenza are more likely to develop severe outcomes compared with hospitalized, vaccinated patients who develop influenza [ 26–28 ]. One study found that significantly more unvaccinated people were admitted to the hospital or died and that vaccination reduced these rates by 23% in people aged 18 years and older [ 28 ].…”
Section: Discussionmentioning
confidence: 99%